Investing in formal on-the-job training: Are SMEs lagging much behind? - Rita K. Almeida; Reyes Aterido (IZA Journal of Labor & Development, 2015)
In a modern economy, the investment in human capital by firms is crucial to foster technological adoption and foster productivity growth. This paper analyzes the correlation between firm size and the investment in job training by employers. Using a large firm level data set across 99 developing countries, we show that a strong and positive correlation in the investment in job training and firm size is a robust statistical finding both within and across countries with very different institutions and levels of development. Even though we cannot fully disentangle correlation from causality, we show that the size-training gap is not fully explained by differences across firms in market imperfections or institutional failures impeding the development of smaller firms. Our findings call for the urgency of collecting better panel data sets to understand how cost-effective are on-the-job training programs in fostering firm productivity and growth in developing countries.
Keywords: J24; D24; 330; On-the-job training; Firm size; Firm level data; Developing countries